Width of Nucleation Region of Si Nanocrystal Grains Prepared by Pulsed Laser Ablation with Different Laser Fluence. (23rd March 2015) - Deng, Zechao; Pang, Xuexia; Ding, Xuecheng; Chu, Lizhi; Wang, Yinglong
Abstract : Si nanocrystal grains were prepared by pulsed laser ablation with different laser fluence in Ar gas of 10 Pa at room temperature. The as-formed grains in the space deposited on the substrates and distributed in a certain range apart from target. According to the depositing position and radius of grains, the nucleation locations of grains in the space were roughly calculated. The results indicated that the width of nucleation region broadened with increasing of ion densities diagnosed by Langmuir probe, which increased with laser fluence from 2 J/cm 2 to 6 J/cm 2 ; that is, width of nucleation region broadened with addition of laser fluence. At the same time, the width broadened with the terminal formation position moving backward and the initial formation position of grains moving toward ablated spot. The experimental results were explained reasonably by nucleation thermokinetic theory.